How Capital Projects are Allocated in Papua New Guinean Villages : The Influence of Local Collective Action, Local-level Institutions, and Electoral Politics - Hasnain, Zahid; Keefer, Philip; Menzies, Nicholas (World Bank, Washington, DC, 2013)
Papua New Guinea (PNG) has implemented numerous institutional changes over the past fifteen years with the avowed aim of bringing government closer to the people, improving accountability and, by extension, local infrastructure development and service delivery. To date however, there has been little empirical evidence to establish whether these changes have impacted the provision of local infrastructure. Similarly, there is little empirical evidence revealing the main political economy factors that influence the way that resources are actually planned, spent, and impact communities at the sub-national level. This report investigates the determinants of local infrastructure projects at the ward level, the lowest level of government in PNG, to assess the impact of these institutional changes and to identify the importance of other factors, in particular local collective action. It does this through a survey covering more than 1000 households across 49 yards in nine PNG districts. It also presents descriptive statistics on the basic characteristics of the households that were surveyed, their knowledge of local level institutions, their participation in groups, and their voting behavior. The report explores especially the determinants of variation within districts in terms of the presence of new projects. Common wisdom in PNG suggests that the home wards of Members of Parliament (MPs) should be especially favored with projects. In six districts, the data includes this ward; these six home wards are no different from other wards in their district with respect to the presence of new projects. The survey asked questions about electoral behavior, the provision of cash and other gifts in exchange for votes and electoral violence. The survey found significant inter-district variation, with vote-buying dramatically higher in the three Highlands districts, where 42 percent of respondents report receiving cash, compared to 9 percent in the other districts. Within districts, vote-buying and the provision of local public works projects are inversely related. Vote-buying is also far more common in the three districts that exhibit the most electoral violence.